Synanthropization of dendroflora near main roads in Białystok (NE Poland) - Łaska, Grażyna (Biodiversity: Research and Conservation, 2015)
The aim of the study was to analyze the species composition of the dendroflora near four main roads in the city of Białystok, taking into regard their geographical and historical origin. The wildlife inventory was conducted in the vegetation season of 2011. The inventory revealed presence of a total of 837 trees and bushes representing 36 species and 18 families. The most abundant trees were those from the family Aceraceae (63.8%), while the most abundant bushes were those representing Rosaceae (48.9%). The contribution of native species (65.7%) was found to be about twice as high as that of alien ones (34.3%). The dominant species among the native trees was Acer platanoides L., while the principal bush species was Crataegus monogyna Jacq. The alien tree species were most commonly represented by Acer negundo L., and bushes - by Ligustrum vulgare L. Spontaneously settled trees and bushes were clearly dominant (59.9%) over those originating from plantations (40.1%). Among the native species of local origin, the prevailing species were synanthropic spontaneophytes (52%), including Acer platanoides and Tilia cordata Mill. Anthropophytes were more abundantly represented by diaphytes (22.7%), followed by kenophytes (10.4%). The most abundant species among diaphytes was Ligustrum vulgare, and among kenophytes - Acer negundo.